Small Firm Death in Developing Countries - McKenzie, David (World Bank, Washington, DC, 2017)
Small firms are an important source of income for the poor in developing countries, and the target of many interventions designed to help them grow. But there is no systematic information on the failure or death of such firms. The paper puts together 16 panel surveys from 12 different developing countries to develop stylized facts from over 14,000 firms on how much firm death there is; on which types of these firms are most likely to die; and on why they die, paying careful attention to issues of measurement and attrition. The authors find small firms die at an average rate of 8.3 percent per year over the first five years of following them, so that half of all firms observed to be operating at a given point in time are dead within 6 years. Death rates are higher for small firms in richer countries, younger firms, retail firms, less productive and less profitable firms, and those whose owners are female and not middle-aged. The paper proposes three theories of why small firms die: firm competition and firm shocks, occupational choice, and non-separability from the household. It finds the cause of firm death to be heterogeneous, with different subgroups of firms more likely to die for reasons consistent with each of these theories.